Bacterial study of some eye drops products and lens sterilizing solutions sold in Syria - حسينو رنا; مرعي منى (Latakia University Journal -Medical Sciences Series, 2023)
Medications instilled directly into the eye are expected to be sterile throughout use. It must also be filed and properly packaged. Recent studies have documented an increase in the incidence of microbial contamination associated with the use of bacteriologically contaminated lens and lens sterilization solutions and eye drops.[1,2,3] This study aims to evaluate the presence of bacterial contamination in multi-dose eye drops and contact lens sterilization solutions marketed in Syria. A total of 75 samples were studied, including 55 eye drops offered for sale in pharmacies in the city of Lattakia, containing active substances with different physiological effects. Also, 20 sterilization solutions for contact lenses offered for sale in pharmacies and cosmetic stores were studied in terms of their bacteriological quality upon opening directly, and the possibility of contamination of these solutions during use for 15 days and 30 days, respectively. Bacterial contamination rates and resulting bacterial species were determined by available methods in the Bacteriological Laboratory, Tishreen University Hospital. A sensitivity test for antibiotics for specific germs was also conducted to find out the degree of pathogenicity and severity of these germs. The results of bacterial culture showed the growth of bacteria in 2.80% of the total number of samples (2 out of 75) when cultured immediately after opening and incubated under appropriate conditions. As for the percentage of samples contaminated with bacteria after 15 days of opening, it was 16.36% of the total number. The percentage of bacterially contaminated samples increased to 24% after 30 days of opening, and lens sterilization solutions accounted for 61.9% of them. Most of the identified bacteria were Escherichia coli, Enterobacter, hemolytic streptococci and non-hemolytic streptococci. The resulting bacteria were resistant to a significant percentage of the broad spectrum antibiotics tested.